A novel approach to promote evidence-based development of district maternal and newborn health plans in two states in India - Harish Kumar; Enisha Sarin; Vaishali Alwadhi; Shailesh Kumar Chaurasia; Kuldeep Singh Martolia; Jaya Swarup Mohanty; Nitin Bisht; Naresh Chandra Joshi; Prasant Kumar Saboth; Sachin Gupta (Wolters Kluwer Medknow Publications, 2022)
Background: Maternal and child health implementation plan development in districts of India lacks systematic process and capacity resulting in suboptimal health improvements. There is ineffective and limited participation and lack of autonomy to effect changes in district priorities. Objectives: Primary objective was to demonstrate a systematic planning approach to develop evidence-based district implementation plans for mothers and children. Methods: A planning tool named RAASTA (RMNCH + A Action Agenda using Strategic Approach for evidence-based district work plans) adapted from WHO (World Health Organization) program review tools was used in the states of Uttarakhand and Jharkhand. The tool was implemented in the two states for the development of implementation plans in a 6-step process by prioritizing district health goals; reviewing maternal, neonatal, child, and family planning intervention coverage; and linking them with activity implementation status; assessing strengths, and weaknesses of previous implementation plans and developing solutions based on current gaps in intervention coverage's. Results: Tool was used for capacity building of 59 participants and also identification of prioritized activities based on their available data. Several newer activities were identified. The districts mainstreamed them as action plans, many of which were incorporated in the state Program Implementation Plan for budgetary provisions under state NHM (National Health Mission) funds. Conclusion: The use of a tool facilitated the systematic development of evidence-based district implementation plans.